Identification of thyroid hormone response genes in the remodeling of dorsal muscle during Microhyla fissipes metamorphosis - Liu, Lusha; Liu, Qi; Zou, Xue; Chen, Qiheng; Wang, Xungang; Gao, Zexia; Jiang, Jianping (Frontiers in Endocrinology, 2023)
Extensive morphological, biochemical and cellular changes have occurred during anuran metamorphosis, which was triggered by a single hormone, thyroid hormone (TH). The function of TH is mainly mediated through thyroid receptor (TR) by binding to the specific thyroid response elements (TREs) of direct response genes, in turn, regulates the downstream genes in the cascade. The remodeling of dorsal skeletal muscle during anuran metamorphosis provides the perfect model to identify the immediate early and direct response genes which are important during apoptosis, proliferation and differentiation of the muscle. In our current study, we performed Illumina sequencing combined with single-molecule real-time (SMRT) sequencing in dorsal muscle of Microhyla fissipes after TH, CHX (cycloheximide) and TH_CHX treatment. We first identified 1,245 differentially expressed transcripts (DETs) after TH exposure, many of which involved in DNA replication, protein processing in endoplasmic reticulum, cell cycle, apoptosis, p53 signaling pathway, and protein digestion and absorption. Comparison of TH group vs Control group and TH_CHX group vs CHX group overlapping gene, 39 upregulated and 6 downregulated genes were identified as the TH directly induced genes. Further analysis indicated AGGTCAnnTnAGGTCA is the optimal target sequence of target genes for TR/RXR heterodimers in M. fissipes. Future investigations on function and regulation of these genes and pathways should help to reveal the mechanisms governing amphibian dorsal muscle remodeling. These full-length and high-quality transcriptomes in this study also provide an important foundation for future studies in M. fissipes metamorphosis.